Identification, Mapping, and Molecular Marker Development for Rgsr8.1: A New Quantitative Trait Locus Conferring Resistance to Gibberella Stalk Rot in Maize (Zea mays L.) - Qian Chen; Jun Song; Wen-Ping Du; Li-Yuan Xu; Yun Jiang; Jie Zhang; Xiao-Li Xiang; Gui-Rong Yu (Frontiers in Plant Science, 2017)
Maize stalk rot is a major fungal disease worldwide, and is difficult to control by chemical methods. Therefore, in maize breeding, quantitative trait loci (QTLs) conferring resistance are important for controlling the disease. Next-generation sequencing technologies are considered a rapid and efficient method to establish the association of agronomic traits with molecular markers or candidate genes. In the present study, we employed QTL-seq, which is a whole-genome resequencing-based approach, to identify candidate genomic regions conferring resistance to maize stalk rot. A novel resistance QTL Rgsr8.1 was finely mapped, conferring broad-spectrum resistance to Gibberella stalk rot (GSR). Segregation analysis in F2 and BC1F1 populations, which were derived from a cross between 18327 (Susceptible) and S72356 (Resistant), indicated that the resistance to GSR was likely to be a quantitatively inherited trait in maize. The result of QTL-seq showed that the resistance to GSR was mapped on chromosome 8 from 161.001 to 170.6 Mb. Based on the simple sequence repeat (SSR) markers, single-nucleotide polymorphism (SNP) markers, and the recombinant test, the location of Rgsr8.1 was narrowed down to 2.04 Mb, flanked by SSR-65 and SNP-25 markers at the physical location from 164.69 to 166.72 Mb based on the maize reference genome. In this region, two candidate resistant genes were found with, one auxin-responsive elements and the other encoding a disease resistance protein. In summary, these results will be useful in maize breeding programs to improve the resistance to GSR in maize.